Kedah ruler s discretion on change of MB - New Straits, Times (New Straith Times, 2016)
Mukhriz Mahathir as Kedah menteri besar lies in the hands of the Sultan of Kedah Tuanku Abdul Halim Mu'adzam Shah, who is also Yang diPertuan Agong, and state Regency Council chairman Tan Sri Tunku Sallehuddin Sultan Badlishah.